The influence of experiential marketing on customer satisfaction and loyalty - Carmo, I. S. do.; Marques, S.; Dias, Á. (Journal of Promotion Management, 2022)
Today, experiences are considered a key differentiating factor for companies as products and services have become similar in terms of their functional attributes. Moreover, individuals' choices are increasingly influenced not only by rational factors, but mainly by emotional factors. This study aims to understand whether the dimensions of experience influence consumer satisfaction and loyalty. The hypotheses were tested using PLS-SEM based on survey data. The results show that satisfaction is influenced positively and directly by affective and sensorial experience and loyalty is influenced positively and directly by affective and behavioural experience. The results also indicate the existence of an indirect relationship between the sensory experience and the affective experience with the loyalty having the mediating effect of satisfaction.